Penatalaksanaan Pasien Wanita 33 Tahun dengan Otitis Media Supuratif Kronik Melalui Pendekatan Kedokteran Keluarga di Puskesmas Campang Raya - Wulandari, Aprilia; Effendi, RE Rizal (Medula, 2023)
Chronic Suppurative Otitis Media (CSOM) is a Chronic inflamationn in the middle ear with perforation of tymphani membrane and characterized by reccurent or persistent mucopurullent otorrhoea more than 2 months. CSOM usually occur in chilhood, most commonly arround two years of age, percentage CSOM in adult 31-35 years old is 6,8%. This case report aims to provide holistic and comprehensive family medicine services by identifying risk factors, clinical problems, management, and prevention of patient complications based on evidence-based medicine while adopting a patient-centered and family-oriented approach. This study is a case report. The primary data were obtained through auto anamnesis, physical examination, and home visits. Meanwhile, the secondary data was obtained from the patient's medical record. The assessment is based on a holistic diagnosis from the beginning, process, and end of the study using qualitative and quantitative methods. Patient Mrs. N 33 years old, female has been diagnosed with CSOM. The internal factor that affects the condition is a lack of knowledge about the triggering factors, while the external factor is due to the family's less awareness of CSOM and its complication prevention. Pharmacological and non-pharmacological interventions were carried out by educating the patient about the prevention of recurrent Chronic Suppurative Otitis Media (CSOM). The diagnosis and management of the patient have been carried out holistically, patient-centered, family-oriented approach, and based on several theories and recent research. As a result of this study, both the patient and the family have progressed to the adoption stage in the behavior change process.